1979
DOI: 10.1073/pnas.76.7.3367
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside inhibition of fibronectin-mediated cell adhesion to collagen.

Abstract: Fibronectin mediates the adhesion of cells to col1agen by first binding to the collagen substrate, followed by attachment of the cells to the fibronectin-collagen complex. Bovine brain gangliosides were found to block fibronectinmediated cell adhesion to collagen in a concentration-dependent manner. The gangliosides did not block the binding of fibronectin to collagen but did prevent the attachment of the cells to the fibronectin-collagen complex. Of the individual gangliosides tested, GT1 and GDia were the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
108
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(112 citation statements)
references
References 32 publications
4
108
0
Order By: Relevance
“…The reactivity of the GM3 in SAM with this antibody was diminished by trypsin treatment of SAM, which suggests that GM3 is not attached directly to the substratum, but indirectly to it through a protein component(s). The fact that the antibody against GM3 did not inhibit cell attachment and spreading on fibronectin confirmed that GM3 is the poorest effector for those phenomena (11,13).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The reactivity of the GM3 in SAM with this antibody was diminished by trypsin treatment of SAM, which suggests that GM3 is not attached directly to the substratum, but indirectly to it through a protein component(s). The fact that the antibody against GM3 did not inhibit cell attachment and spreading on fibronectin confirmed that GM3 is the poorest effector for those phenomena (11,13).…”
Section: Resultsmentioning
confidence: 64%
“…Using the conventional antibody against GM3, Hakomori et al found that the reactivity of GM3 to that antibody was higher in * To whom correspondence should be addressed These observations suggest that GM3 may have an important function(s) in cellto-cell or cell-to-substrate interaction. GM3 has, however, been reported to be the poorest effector for cell attachment (11) and spreading (13) to fibronectin and in the organization of extra cellular fibronectin into the fibrillar form (17).…”
mentioning
confidence: 99%
“…A number of reports have indicated that the exogenous addition of polysialogangliosides to fibronectin-attached cells caused them to round up and detach from the substrate (18,29,49). These studies led to the conclusion that gangliosides may act as specific fibronectin receptors.…”
Section: Discussionmentioning
confidence: 94%
“…Direct evidence is provided that GD2 is involved in M21 cell attachment to fibronectin, since treatment of these cells with anti-GD2 monoclonal antibodies causes cell rounding and detachment from a fibronectin substrate. Moreover, scanning electron microscopy demonstrates that this loss of attachment of fibronectin is characterized by a perturbation of the cell attachment-promoting microprocesses that in the presence of these antibodies lose contact with the fibronectin substrate.umber of studies have indicated that the carbohydrate moiety of gangliosides plays a direct role in cellsubstratum interactions, thus implicating them as putative cell surface receptors for fibronectin and collagen (8,18,29,49). In a previous paper, we used monoclonal antibodies (Mabs) ~ that specifically recognize carbohydrate determinants on the gangliosides GD2 and GD32 (8) to localize them on the surface of human melanoma cells and their focal adhesion plaques.…”
mentioning
confidence: 99%
See 1 more Smart Citation